Tempos e espaços na rotina de uma creche do município de São Bernardo do Campo após o retorno presencial - Leal, Priscila de Oliveira (2023)
The present research has as object of study the times and spaces in the routine of a day care center in the city of São Bernardo do Campo. Thus, it is motivated by the following questions: What do the teachers of the researched day care center understand about times and spaces? How did the organization of times and spaces occur in a day care center in the municipality of São Bernardo do Campo during the covid-19 pandemic? The general objective is to analyze how the organization of times and spaces occurred in a day care center in the municipality of São Bernardo do Campo during the pandemic. As for the specific objectives, they are: to understand what the teachers understand about times and spaces in the day care center; and verify if the organization of times and spaces in the day care routine occurs according to the children's needs. Thus, we started from the hypothesis that the organization of times and spaces in the systematically elaborated routine for children interferes with their development, as it does not meet children's needs. The research universe corresponds to a day care center in the city of São Bernardo do Campo, and the participants are: four children, four teachers and a pedagogical coordinator, all belonging to the school unit. This is a qualitative research, and the instruments for data production were: story wheel and conversation with the children, observation of the teachers' routine, as well as semi-structured interviews with them and with the coordinator. In addition, we emphasize what the Political-Pedagogical Project of the institution and the current legislation, at the federal and municipal levels, say. After content analysis, in the light of Bardin's proposal, two categories emerged, namely: “organization of times and spaces in the day care center”; and “pandemic and qualitative loss of interactions”. The theoretical framework used to support the first category was based on authors of critical pedagogy, namely: Miguel Angel Zabalza, Maria da Graça Souza Horn, Maria Carmen Silveira Barbosa and Adriana Fiedmann. With regard to the second category, the contributions of Marta Kohl de Oliveira. The results show that the principles to guide the organization of times and spaces are present in municipal and federal documents, but the teachers are unaware of them. Therefore, the adultcentric posture is strongly marked in the institution. Children do not have freedom of choice, and the determination of the time established for their action is carried out by adults in the face of an institutionally elaborated routine. With the arrival of the pandemic, the conception of controlled times and spaces became even more rigid, since with the return of face-to-face activities, it was necessary to adopt preventive measures, such as separating children into groups and delimiting environments.